80.6k views
3 votes
Find the turning point of y=h(x) if h(x)=f(-x)f(x)=x^2-4x+12

User AChampion
by
5.2k points

1 Answer

5 votes

Given:


y=h(x)\text{ where }h(x)=f(-x)\text{ and }f(x)=x^2-4x+12.

Required:

We need to find the turning point of y=h(x).

Step-by-step explanation:

Replace x =-x in the function f(x) to find h(x).


f(-x)=(-x)^2-4(-x)+12.
f(-x)=x^2+4x+12.

Replace f(-x)=y in the equation.


y=x^2+4x+12.
y=x^2+2*2x+4+8.
y=x^2+2*2x+2^2+8.
Use\text{ }(a^2+2ab+b^2)=(a+b)^2.
y=(x+2)^2+8.

Which is of the form


y=a(x-h)^2+k.

where a=1, h=-2, and k=8.

The point (h,k)=(-2,8) is the turning point.

Final answer:

The turning point of y=h(x) is (-2,8).

User Zbinsd
by
5.3k points